A unique case of kidney’s collecting system MALT lymphoma - Asgari, Seyed Alaeddin; Baghani Aval, Hamidreza; Asgari, Seyed Ali; Kheradmand, Keyvan (Canadian Urological Association Journal, 2014)
<!--[if gte mso 9]> <![endif]--> Low-grade B cell lymphomas of mucosa-associated lymphoid tissue (MALT lymphomas) are mostly seen in the gastrointestinal tract. MALT lymphomas involving kidney are extremely rare. We report on a case of MALT lymphomas of the kidney. A 74-year-old woman presented with an episode of gross hematuria and right flank pain. In renal sonography, we found a hypoecho lesion measuring 61 × 58 × 44 mm in the lower pole of right kidney. A computed tomography scan revealed an enlarged hypodense soft tissue measuring 62 × 42 × 37 mm within the pelvic brim of the right kidney, with extension to the proximal portion of the ipsilateral ureter and engulfed it. The patient underwent a right radical nephrectomy. The pathology specimen indicated a lymphoprolifrative disorder involving the kidney and ureter. To obtain a definitive diagnosis, we used an immunohistochemistry, which confirmed the diagnosis of a MALT lymphoma. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->